New endemic platyrrhine humerus from Haiti and the evolution of the Greater Antillean platyrrhines. Issue 91 (February 2016) - Tallman, Melissa; Cooke, Siobhán B.
Abstract: Much debate surrounds the phylogenetic affinities of the endemic Greater Antillean platyrrhines. Thus far, most phylogenetic analyses have been constructed and tested using craniodental characters. We add to this dialog by considering how features of the distal humerus support or refute existing hypotheses for the origins of fossil Caribbean primates, utilizing three-dimensional geometric morphometric data in combination with character based cladistic analyses. We also add to the sample of fossil platyrrhine humeri with the description of UF 114718, a new distal humerus from Haiti. We reconstruct UF 114718 to be a generalized, arboreal quadruped attributed to the species Insulacebus toussantiana . Our results from phylogenetic analyses lend some support to the idea that some Greater Antillean fossil taxa including Xenothrix mcgregori, Antillothrix bernensis, and Insulacebus toussaintiana could form a monophyletic clade that is sister to either extant Platyrrhini or basal pitheciids. Based on the distal humeral data, we reconstruct the earliest ancestral platyrrhine to be a generalized, arboreal quadruped that potentially emphasized pronated arm postures during locomotion and may have engaged in some limited climbing, most similar in shape to early anthropoids and some of the earliest Antillean forms. However, aspects of shape and standard qualitative characters relating to the distal humerus seem to be variable and prone to both homoplasy and reversals; thus these results must be interpreted cautiously and (where possible) within the context provided by other parts of the skeleton.